MRI features in the non-traumatic spinal cord injury patients presenting at the Korle Bu Teaching Hospital, Accra - Gbadamosi, H.; Mensah, Y.B.; Asiamah, S. (Ghana medical journal, 2018)
Background: Neurological limb deficit due to non-traumatic myelopathy is a disabling and distressing neurological condition. In recent time Magnetic Resonance Imaging (MRI) has proven to be the ultimate imaging modality for evaluating pathologies of the spinal cord. Objective: To describe the Magnetic Resonance Imaging (MRI) features of patients with Non-Traumatic Spinal Cord Injury evaluated at the Korle Bu Teaching Hospital. Methods: A descriptive cross-sectional study was carried out at the Korle Bu Teaching Hospital (KBTH), Accra, Ghana. Results: Out of a total of 141 MRI’s evaluated 60.3% were males and 39.7% female. The majority of the respondents 85.1% had paraparesis/paraplegia,13.5% had quadriparesis/quadriplegia, 1.4% had weakness in one upper limb and both lower limbs. The commonest MRI features of NTSCI recorded was due to degenerative disease of the spine 75.9%, spinal metastases 5.7%, Pott's/pyogenic spondylitis 3.5%, demyelinating disease 2.8% and primary spinal tumours 2.8%. Conclusion: The commonest MRI findings in the study population were due to degenerative disease of the spine, followed by spinal metastases and infective spondylitis.
Keywords: Paraparesis; Paraplegia; Tetraparesis; Tetraplegia; Magnetic Resonance Imaging